The impact of corporate governance on executive directors’ remuneration of listed small and medium scale firms in Malaysia - Ab Rashid, Hafiz-Majdi; Annuar, Hairul Azlan (2019)
ABSTRACT The study examines the relationship between corporate governance on directors’ remuneration of listed small and medium scale firms in Malaysia over the period of 2012 to 2015 on the 274 listed small and medium enterprises on the Bursa Malaysia. Six potential corporate governance mechanisms were utilised as surrogates which include Size, executive ownership, CEO duality, family relationship, independent non-executive directors on the remuneration committee, and board meetings and amount of remuneration package of all the directors was used as dependent variables. The study estimate the data so collected using static OLS regression and further control for potential endogeneity among the variables with system dynamic generalised method of moment. The results from ordinary least square regression indicate that four corporate governance mechanisms have significant impact on the directors’ remuneration among the small and medium enterprises listed on Bursar Malaysia. However, due to some inherent shortcoming of this estimator, the study estimates system dynamic generalised method of moment. The result from this estimate reveal that five out of six corporate governance mechanisms are significantly affect the directors’ remuneration among listed small and medium enterprises in Malaysia. The study concludes that CEO duality, board size, directors’ ownership, presence of independent director on the remuneration committee and board meetings have significant impact of directors’ remuneration among listed small and medium enterprises in Malaysia. Hence, the study recommend that the regulators should consider these factors in order to minimise the agency problem in this category of listed in the country. Though, the findings from this study confirm the proposition upon which agency theory was developed, the scope of the study is limited to small firms, thus, the generalisation the findings to large firms might be feasible.